Metodologi Pembelajaran Fiqih Berbasis Daring pada Mahasiswa S1 PAI Semester III di UIN Sunan Kalijaga Yogyakarta - Doli Habibi Wijaya Panjaitan; Mahmud Arif; Muchtar Falahain; Radino Radino (Tafhim Al-'Ilmi, 2022)
Â Abstract Methodology is the best and most effective way, so the work order in a method must be scientifically calculated. Hence a method is always part of the experiment. Learning is a combination composed of human elements, materials, facilities, equipment and procedures that influence each other in achieving the ultimate goal of learning. The fiqh learning methodology is a method taken by educators in conveying Islamic laws relating to human life, both those relating to God and those relating to humans. In this learning, a way is needed to convey messages to students which will later become guidelines in everyday life. This study aims to determine the online-based methodology of Islamic jurisprudence learning for third semester PAI students at UIN Sunan Kalijaga Yogyakarta. This type of research is a field research (filed research) with a descriptive qualitative approach. Interviews, and directly following the learning in class are the methods used in data. The results of this study, show that the courage-based learning of fiqh used by PAI students in the third semester of UIN Sunan Kalijaga, is by using the Wattsapp Group media and Zoom Meeting combined with the group discussion method. In its application, learning runs without obstacles. However, continuous learning boldly is boring, because students only use audio-visual media. Likewise, in their understanding of learning, it is considered unnatural and remembers long-lasting memories, because students answering problems are still focused on the internet. Keywords: Methodology, fiqh learning, online